Blended Learning as an Effective Learning Solution on Intensive English Program in the New Normal Era - Budiarti Putri Putri Uleng; Musyrifah Mahfuddin; Nadya Nurhidayah (Jurnal Andi Djemma | Jurnal Pendidikan, 2022)
The government implemented new normal policies in various areas, including education, during this new normal era, including the reopening of schools. Several political parties, particularly parents, have expressed strong opposition to the new policy. Many of them are concerned that their children will have to attend school outside until the COVID-19 pandemic is over. In this situation, the school community must adapt to this new normal by adhering to the government's health protocols. The lecturer, as the primary learning facilitator, is crucial in shaping new student habits. Learning innovation and the use of appropriate and diverse learning media work against the improvement in educational quality in the new peacetime era. The use of blended learning in Intensive English classes, which combines face-to-face and online learning with advanced techniques, is one of the best learning model solutions for adapting to the new normal era. The purpose of this research is to explain blended learning as a type of learning solution on the Intensive English Program at Andi Djemma University as a form of adaptation to the new normal era. In this study, we used descriptive qualitative techniques to collect data on the facts of implementing blended learning in the Intensive English Program and the current phenomena of student behavior associated with this learning model. The study's findings revealed that blended learning allows students to practice conversation during English lessons and can improve learning outcomes and scores, particularly when speaking. Firstly, 67.1% of students said that blended learning is effective, efficient, attractive, and can be used very effectively. Secondly, 77 students (84.7%) prefer blended learning to complete online or face-to-face learning.